Poważny brak rozeznania oceniającego (kan. 1095 n. 2 KPK) oraz wykluczenie nierozerwalności małżeństwa (kan. 1101 § 2 KPK) w świetle wyroku Trybunału Roty Nuncjatury Apostolskiej w Hiszpanii c. Morán Bustos z 9 lipca 2007 r. - Białobrzeski, Tomasz (Ius Matrimoniale, 2013)
Presented sentence of the Tribunal of the Rota of the Apostolic Nunciature in Spain adjudicate definitely in II instance adjudication nulitatis matrimonii by virtue of grave defect of discretion of judgment concerning by both parties (can. 1101 § 2 CCL) and lack of the freedom internal also by both parties (can. 1095 n 2 CCL). The question which was considering concerned matrimony which was got in 15.03.1972. The libellus was lodged in 26.04.1996. Tribunal I instance in sentence of 15.11.2000 declared that there was no proved the nullity of the marriage. The petitioner lodged appeal to the Rote of the Spain. In 09.07.2009 the Rote declared the validity of the marriage.